DAMPAK MODERNISASI FASHION TERHADAP REMAJA DI BANGKO DALAM KARYA SENI LUKIS REALIS KONTEMPORER - Ir. Drs. heldi, M.Si., Ph.D., RIZKY BUDI ARRAHMAN, Dra. Jupriani, M.Sn., (Jurusan Seni Rupa FBS UNP Padang, 2018)
The purpose of the idea of the creation of this final work is to visualize the impact of fashion modernization on youth in Bangko which is expressed through contemporary realist painting to inform the world of the impact of fashion modernization that influences the way dress behavior.The method of creating this final paper uses five stages: preparatory, elaboration, synthesis, concept realization and completion. Using acrylic paint on canvas and flat brush strokes and colors that match the subject, with a contemporary realist style. Ten works are created telling about the impact of fashion modernization on teenagers with the title: 1.Sakit Senang, 2.Seksi, 3.Bungkusan, 4.Tak Terkalahkan, 5.Boho, 6.Berani kan ?, 7.Panas, 8.Ngintip, 9.Teralihkan, 10.Centil. This work can be used as recording the history of Bangko teenagers today.Kata kunci: Modernisasi, Fashion, Remaja, Realis Kontemporer